Modal Politik dan Modal Sosial Athari Gauthi Ardi Pada Kemenangan Pemilu Legislatif Tahun 2019 di Provinsi Sumatera Barat - Reninta Ananda; Tengku Rika Valentina (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2021)
In the 2019 legislative elections in West Sumatra, social capital and political capital are one of the ways in which actors can compete with their political opponents, in order to attract the attention of the public to support it. Birner and Witmer state that the concept of political capital makes it possible to study local communities using social capital to achieve political goals, and Bourdieu also said that social capital is in the form of actual and potential resources owned by someone from an institutionalized and ongoing social network that provide collective support for its members. The focus of this study is to explain how Athari Gauthi Ardi used Political Capital and Social Capital as a tool to win himself in political contestation in the 2019 legislative elections. Parental power used by Athari Gauthi Ardi to win the 2019 legislative elections in West Sumatra. Researchers' assumptions emerge that one of Athari Gauthi Ardi's capitals is political capital owned by his parents. The purpose of this study is to determine the political capital and social capital utilized by Athari Gauthi Ardi in the 2019 legislative elections and the relationship between political capital and social capital to Athari Gauthi Ardi's victory in the 2019 legislative general election. This study used study case qualitative methods. The results of this study indicate that Athari Gauthi Ardi has sufficient capital, such as : (1) Parent's network and Ali Mukhni's network are used by Athari Gauthi Ardi. (2) Political support obtained by Athari Gauthi Ardi from the community, religious and traditional leaders, the PAN Party, and regional cadres from the West Sumatra of PAN party. (3) Athari Gauthi Ardi was intelligent woman with a tough personality, diligent and also can mingle with the community. (4) As well as sufficient economic capital owned by Athari Gauthi Ardi and his parents, who is a successful businessman.